Preparation and properties of HfB2-HfC and HfB2-HfC-MoB composites by reactive spark plasma sintering - Yangshuo Bai; Weixia Shen; Chao Fang; Liangchao Chen; Qianqian Wang; Biao Wan; Xiaopeng Jia; Yuewen Zhang; Zhuangfei Zhang (Journal of Asian Ceramic Societies, 2023)
ABSTRACTUltra-high-temperature ceramics are required for many aerospace applications. In this work, HfB2-30 vol.% HfC and HfB2-26 vol.% HfC-43 vol.% MoB high-density composites were prepared by one-step in-situ reactive spark plasma sintering (R-SPS) using Hf, B4C and Mo powders as starting materials. The influences of sintering temperature on the densification mechanism, microstructural evolution, mechanical properties and oxidation resistance of the composites were thoroughly investigated. The results demonstrate that the raw materials undergo a complete chemical reaction to form new binary HfB2-HfC and ternary HfB2-HfC-MoB composite structures at a temperature of 1300°C. The HfB2-HfC and HfB2-HfC-MoB composites prepared at the optimal conditions (pressure = 50 MPa, temperature = 1800°C, holding time = 5 min) had highre densities of 97% and 98%, respectively. The Vickers hardness, Young’s modulus and fracture toughness of the HfB2-HfC composite were 18.3 GPa, 525 GPa and 6.34 MPa·m1/2, respectively. However, after molybdenum was added, the Vickers hardness of the ternary HfB2-HfC-MoB composite increased to 19.4 GPa but its fracture toughness decreased slightly to 6.1 MPa·m1/2. Compared with the binary composite, the ternary composite exhibited a low and thermally stable oxidation rate up to a temperature of 1400°C, and the test was conducted in air atmosphere.